Autoimmune Hepatitis—Immunologically Triggered Liver Pathogenesis—Diagnostic and Therapeutic Strategies. (25th November 2019) - Sucher, Elisabeth; Sucher, Robert; Gradistanac, Tanja; Brandacher, Gerald; Schneeberger, Stefan; Berg, Thomas
Abstract : Autoimmune hepatitis (AIH) is a severe liver disease that arises in genetically predisposed male and female individuals worldwide. Diagnosis of AIH is made clinically applying diagnostic scores; however, the heterotopic disease phenotype often makes a rapid determination of disease challenging. AIH responds favorably to steroids and pharmacologic immunosuppression, and liver transplantation is only necessary in cases with acute liver failure or end-stage liver cirrhosis. Recurrence or development of de novo AIH after transplantation is possible, and treatment is similar to standard AIH therapy. Current experimental investigations of T cell-mediated autoimmune pathways and analysis of changes within the intestinal microbiome might advance our knowledge on the pathogenesis of AIH and trigger a spark of hope for novel therapeutic strategies.